The Use of Teaching Factory-Based Learning Models to Optimize Social Science Learning Outcomes Among Vocational School Students - Sarjoko Sarjoko; Indah Widyastuti; Suharno Suharno; A.G Tamrin; Budi Tri Cahyono (Teknodika, 2026)
This study explores the use of a teaching factory-based learning model to optimize Natural and social sciences learning outcomes in Vocational High Schools. Teaching Factory emerged as an innovative solution that bridges vocational education and the industrial world by integrating real production experiences into learning. This model not only equips students with technical skills but also prepares them to face the complexities of the world of work. This study uses a mixed methods approach with the Exploratory Sequential Design method, starting with a qualitative exploration to understand learning phenomena, followed by a quantitative method to test qualitative findings. Data was collected through participatory observation, in-depth interviews, document analysis, and learning experiments. The results of the study show that the Teaching Factory has excellent potential to increase the relevance of science learning, develop students' practical skills, and motivate students. However, its implementation faces challenges such as limited resources and a lack of institutional support. This research emphasizes the importance of the Teaching Factory as an effective learning model in vocational education, with implications for curriculum development, teacher training, and industry collaboration.